CCDC92 promotes podocyte injury by regulating PA28α/ABCA1/cholesterol efflux axis in type 2 diabetic mice - Zuo Fu-wen; Liu Zhi-yong; Wang Ming-wei; Du Jun-yao; Ding Peng-zhong; Zhang Hao-ran; Tang Wei; Sun Yu; Wang Xiao-jie; Zhang Yan; Xie Yu-sheng; Wu Ji-chao; et al. (Acta Pharmacologica Sinica; Vol 45, No 5 (May 2024): Acta Pharmacologica Sinica, 2024)
Podocyte lipotoxicity mediated by impaired cellular cholesterol efflux plays a crucial role in the development of diabetic kidney disease (DKD), and the identification of potential therapeutic targets that regulate podocyte cholesterol homeostasis has clinical significance. Coiled-coil domain containing 92 (CCDC92) is a novel molecule related to metabolic disorders and insulin resistance. However, whether the expression level of CCDC92 is changed in kidney parenchymal cells and the role of CCDC92 in podocytes remain unclear. In this study, we found that Ccdc92 was significantly induced in glomeruli from type 2 diabetic mice, especially in podocytes. Importantly, upregulation of Ccdc92 in glomeruli was positively correlated with an increased urine albumin-to-creatinine ratio (UACR) and podocyte loss. Functionally, podocyte-specific deletion of Ccdc92 attenuated proteinuria, glomerular expansion and podocyte injury in mice with DKD. We further demonstrated that Ccdc92 contributed to lipid accumulation by inhibiting cholesterol efflux, finally promoting podocyte injury. Mechanistically, Ccdc92 promoted the degradation of ABCA1 by regulating PA28α-mediated proteasome activity and then reduced cholesterol efflux. Thus, our studies indicate that Ccdc92 contributes to podocyte injury by regulating the PA28α/ABCA1/cholesterol efflux axis in DKD.